Masked Semantic/Associative and Translation Priming Across Languages - Ali Akbar Ansarin; Shalale Javadi (East European Journal of Psycholinguistics, 2018)
The present study was an attempt to investigate bilingual mental lexicon. The main question addressed in the study was whether semantic/associative and translation priming effects could be achieved with Persian-English bilinguals. The masked priming paradigm, as a technique reflecting automatic cognitive processes going on during semantic processing rather than strategic uses of the prime, was deployed to answer the question. Four types of prime-target pairs (translation equivalent, semantically similar, associatively related, and semantically associated pairs) were formed for the purpose of the lexical decision task. A total of 85 Persian-English bilinguals participated in the study. Though the priming effect was not found for the first three groups, the targets in semantically associated pairs (most strongly related words) responded about 29 ms faster. The results suggested that bilinguals share mental representations for associatively semantically related words; consequently, teaching new words of the second language by linking them to associatively related words of the first language may lead to better results. References Balota, D. A., & Lorch, R. F. (1986). Depth of automatic spreading activation: Mediated priming effects in pronunciation but not in lexical decision. Journal of Experimental Psychology: Learning, Memory, Cognition, 12, 336–345. Chiarello, C., Burgess, C., Richards, L., & Pollock, A. (1990). Semantic and associative priming in the cerebral hemispheres: Some words do, some words don’t…Sometimes, some places. Brain and Language, 38, 75–104. Collins, A. M., & Loftus, E. F. (1975). A spreading activation theory of semantic priming. Psychological Review, 82, 407–428. Coltheart, M. (1981). The MRC Psycholinguistic Database. Quarterly Journal of Experimental Psychology, 33A, 497–505. Costa, A., Colome, A., & Caramazza, A. (2000). Lexical access in speech production: The bilingual case. Psicologica, 21, 403–437. de Groot, A. M. B., & Nas, G. L. (1991). Lexical representation of cognates and non-cognates in compound bilinguals. Journal of Memory and Language, 30, 90–123. Dijkstra, A. F. J., & Van Heuven, W. J. B. (2002). The architecture of the bilingual word recognition system: From identification to decision. Bilingualism: Language and Cognition, 5(3), 175-197. Duyck, W. (2005). Translation and associative priming with cross-lingual pseudohomophones: Evidence for nonselective phonological activation in bilinguals. Journal of Experimental Psychology: Learning, Memory, and Cognition, 31, 1340–1359. Fischler, I. (1977). Semantic facilitation without association in a lexical decision task. Memory & Cognition, 5, 335–339. Forster, K. I., & Davis, C. (1984). Repetition priming and frequency attenuation in lexical access. Journal of Experimental Psychology: Learning, Memory, and Cognition, 10, 680–698. Forster, K. I., & Forster, J. C. (2003). DMDX: A Windows display program with millisecond accuracy. Behavior Research Methods, Instruments, & Computers, 35(1), 116–124. Fotovatnia, Z., & Taleb, F. (2012). Masked noncognate priming across Farsi and English. Journal of Teaching Language Skills, 4(1), 25–48. French, R. M., & Jacquet, M. (2004). Understanding bilingual memory. Trends in Cognitive Science, 8, 87–93. Grainger, J., & Frenck-Mestre, C. (1998). Masked priming by translation equivalents in proficient bilinguals. Language and Cognitive Processes, 13(6), 601–623. Jiang, N., & Forster, K. I. (2001). Cross-language priming asymmetries in lexical decision and episodic recognition. Journal of Memory and Language, 44(1), 32–51. Kotz, S. A. (2001). Neurolinguistic evidence for bilingual language representation: A comparison of reaction times and event-related brain potentials. Bilingualism: Language and Cognition, 4, 143–154. Kroll, J. F., & Stewart, E. (1994). Category interference in translation and picture naming: Evidence for asymmetric connections between bilingual memory representations. Journal of Memory and Language, 33,149–174. Lupker, S. J. (1984). Semantic priming without association: A second look. Journal of Verbal Learning and Verbal Behavior, 23, 709–733. Perea, M., Duñabeitia, J. A., & Carreiras, M. (2008). Masked associative/semantic priming effects across languages with highly proficient bilinguals. Journal of Memory and Language, 58, 916–930. Perea, M., & Rosa, E. (2002). The effects of associative and semantic priming in the lexical decision task. Psychological Research, 66, 180–194. Samani, R., & Sharifian, F. (1997). Cross-language hierarchical spreading of activation. In Sharifian, F. (ed.), Proceedings of the Conference on Language, Cognition, and Interpretation (pp. 11–23). Isfahan: IAU Press. Sanchez-Casas, R. M., Davis, C. W., & Garcia-Albea, J. E. (1992). Bilingual lexical processing: Exploring the cognate/non-cognate distinction. European Journal of Cognitive Psychology Special Issue: Multilingual Community, 4(4), 293–310. Williams, J. N. (1994). The relationship between word meanings in the first and second language: Evidence for a common, but restricted, semantic code. European Journal of Psychology, 6, 195–220.